The Application of Maximum Principle in Supply Chain Cost Optimization - Zhou Ling; Wang Jun (Institute of Advanced Engineering and Science, 2014)
In this paper, using the maximum principle for analyzing dynamic cost, we propose a new two-stage supply chain model of the manufacturing-assembly mode for high-tech perishable products supply chain and obtain the optimal conditions and results. On this basis, we further research the effect of localization of CODP on the total cost and the relation of CODP, inventory policy and demand type through the data simulation. The results of simulation show that CODP locates in the downstream of the product life cycle, is a linear function of the product life cycle. The result indicates that the demand forecast is the main factors influencing the total cost; meanwhile the mode of production according to the demand forecast is the deciding factor of the total cost. Also the model can reflect the relation between the total cost of two-stage supply chain and inventory, demand. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3807